2001
DOI: 10.1054/jhsb.2000.0566
|View full text |Cite
|
Sign up to set email alerts
|

Free Vascularized Toe Joint Transfer to the Hand. A Technique for Simultaneous Reconstruction of the Soft Tissue

Abstract: Twelve patients underwent reconstruction of injured finger joints using our technique of a vascularized transfer of the second toe proximal interphalangeal joint. The age of the patients at operation ranged from 7 to 47 years and the postoperative follow-up was 9 to 48 months. All the joint transfers survived and united with resolution of the preoperative joint pain, deformity and instability. The average range of motion of the reconstructed joints was 59 degrees in the proximal interphalangeal and 54 degrees … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
30
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 8 publications
0
30
0
3
Order By: Relevance
“…Cependant, ils confirment à un recul moyen de 15 ans (10-22) l'absence de dégradation de l'interligne articulaire à la radiographie. Kimori et al [13] procèdent à une excision large de l'ensemble des tissus lésés sur le doigt receveur (tendon extenseur, peau) et une reconstruction en un temps moyennant le prélèvement d'un large lambeau cutané à la face dorsale du pied. L'arc de mobilité moyen semble meilleur par cette technique (598) mais la rançon cicatricielle est considérable.…”
Section: [ ( ) T D $ F I G ]unclassified
See 1 more Smart Citation
“…Cependant, ils confirment à un recul moyen de 15 ans (10-22) l'absence de dégradation de l'interligne articulaire à la radiographie. Kimori et al [13] procèdent à une excision large de l'ensemble des tissus lésés sur le doigt receveur (tendon extenseur, peau) et une reconstruction en un temps moyennant le prélèvement d'un large lambeau cutané à la face dorsale du pied. L'arc de mobilité moyen semble meilleur par cette technique (598) mais la rançon cicatricielle est considérable.…”
Section: [ ( ) T D $ F I G ]unclassified
“…Arthrodèse transitoire en rectitude, suture sous forte tension de l'appareil extenseur et appareillage dynamique en extension ont pour objectif de limiter ce déficit. Kimori et al [13], par la reconstruction systématique de la peau dorsale et des bandelettes latérales le cas échéant, semble parvenir à limiter ce déficit sans que cela se fasse au détriment de la flexion mais au prix d'une rançon cicatricielle majorée. Foucher et al [16] proposent de sous-dimensionner le transplant afin de limiter sa tendance à la flexion et de suturer les poulies natives à la berge de la gaine, évitant l'effet corde d'arc du tendon fléchisseur.…”
Section: [ ( ) T D $ F I G ]unclassified
“…[1][2][3][4][5][6][7][8][9][10] In 1967 Buncke et al 11 reported the successful transfer of a free vascularized MCP joint of a severely traumatized index finger to the PIP joint of the adjacent middle finger. Further studies have shown improved results with vascularized joint transfers compared with nonvascularized joint transfers.…”
mentioning
confidence: 99%
“…12 Two types of joints can be used for reconstruction of the MCP joint of the hand: the PIP joint and the metatarsophalangeal (MTP) joint of the second or third toe. [1][2][3]5,8,9 Two techniques for MTP joint transfer have been reported: a technique in which the joint is turned 180°around its longitudinal axis and a technique in which the joint is not turned. 1,8,9 In the reversal process the dorsal surface is placed palmar and the palmar surface is placed dorsal.…”
mentioning
confidence: 99%
See 1 more Smart Citation